Beyond the surface: confronting the impact of topical steroids on facial skin - Patel, Krut J.; Lakhani, Som J.; Patel, Shreya D. (International Journal of Research in Dermatology, 2024)
Background: Topical steroids have become the primary therapeutic approach among dermatologists. The clinical outcomes are attributed to their anti-inflammatory, antiproliferative, and immunosuppressive effects. However, this miraculous remedy can lead to significant trouble when used improperly, especially on the face where it can lead to topical steroid damaged faces (TSDF). Methods: study was conducted for 9 months among 30 patients presenting with chief complaints due to topical steroid abuse over face and data was collected and analysed after using self-designed open ended questionnaire. Results: Out of 30 patients, preponderance were seen in females (M:F=1:2.3) The most common age group was 18-28 years (50%). Majority of them (36.6%) used class-3 of highly potent steroid which is betamethasone valerate 0.1%. Most common indication for application was as fairness cream (46.7%). In majority of the patients (70%), suggestion for application was given by pharmacist. 73.3% of patients, purchase medication over the counter (OTC) without prescription. Duration of usage was more than 6 months in 10% patients. Dyspigmentation (32.1%) followed by erythema (28.6%) were the most common adverse effects. Conclusions: Using too many topical corticosteroids may benefit manufacturers and sellers, but it harms unsuspecting people. It’s crucial to evaluate and advise patients, as well as inform doctors about avoiding excessive use of these products on the face. This is an important step that needs attention now.